Potential application of nanotechnology in formulating biofertilizers as a sustainable way for promoting plant growth: a systematic review - Massawe, Ikunda Herman; Mbega, Ernest; Meya, Akida I. (Frontiers in Sustainability, 2025)
IntroductionNanoparticles and Plant Growth-Promoting Microbes are trending as sustainable means for supplying plant nutrients. The purpose of this review was to understand how these technologies have been applied together to enhance plant growth.MethodsA PRISMA protocol was followed to explore relevant articles that reported the impact of nanoparticles on plant growth-promoting microbes or their influence on plant growth. By using the established search string, 70 original research articles published between 2000 and 2023 from Google Scholar and Scopus were obtained.ResultsThe results show that 21 microbe genera with more than 50 species can promote plant growth. Free-living plant growth-promoting rhizobacteria are the most studied microbes, followed by arbuscular mycorrhizal fungi. Inorganic nanoparticles, such as ZnO, are the most extensively studied nanoparticles, followed by organic nanoparticles, primarily chitosan.DiscussionNanoparticles and plant growth-promoting microbes can be applied as separate treatments or by formulating nano-biofertilizer, and their combination ameliorates biotic and abiotic plant growth stresses. The effect of nanoparticles on plant growth-promoting microbes is concentration and species-dependent.